Kepala Sekolah Sebagai Pemimpin (Leader) Dalam Meningkatkan Profesionalisme Guru Di Madrasah Tsanawiyah Muhammadiyah 02 Aimas Kabupaten Sorong - Khatipah Khatipah; Hermanto Hermanto (Pascasarjana IAIN Sorong, 2021)
This study was conducted to obtain an overview of the role of the principal as a leader in improving teacher professionalism at Madrasah Tsanawiyah (MTs) Muhammadiyah 2 Aimas, Sorong Regency. This research uses descriptive qualitative with case study design. The subjects of this research are Principals, Foundations, Supervisors, Ministry of Religion, Teachers and Administrative Employees. Data were collected by in-depth interview, observation and documentation techniques. The data were analyzed using a qualitative descriptive technique from Milas and Huberman, namely data reduction, display and data verification. The results of this study are the principal's role as a leader, namely: giving instructions and supervision, developing the vision and mission, motivating teachers in order to increase teacher professionalism, and delegating tasks to teachers in improving their performance.